2021
DOI: 10.1177/21925682211052003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes in Percutaneous Fixation of Traumatic Fractures between Ankylosing Spondylitis and Diffuse Idiopathic Skeletal Hyperostosis

Abstract: Study Design Retrospective cohort study. Objectives This study aims to analyze outcomes and complications of patients with thoracic and lumbar fractures in the setting of ankylosing spinal disorders (ASD) treated with minimally invasive surgery (MIS). Methods The operative logs from 2012 to 2019 from one academic, Level I trauma center were reviewed for cases of thoracic and lumbar spinal fractures in patients with ASD treated with a MIS approach. Variables were compared between patients with ankylosing spondy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In recent years, minimally invasive surgery has been recognized by the majority of doctors, especially for elderly AS patients with more underlying diseases. It can achieve better clinical results and reduce the occurrence of surgical complications [ 9 , 10 , 29 , 30 ]. Ye et al [ 9 ] demonstrated that minimally invasive surgery can achieve effects similar to those of traditional open surgery, while reducing bleeding, trauma, and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, minimally invasive surgery has been recognized by the majority of doctors, especially for elderly AS patients with more underlying diseases. It can achieve better clinical results and reduce the occurrence of surgical complications [ 9 , 10 , 29 , 30 ]. Ye et al [ 9 ] demonstrated that minimally invasive surgery can achieve effects similar to those of traditional open surgery, while reducing bleeding, trauma, and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…10 Fusion surgery for OVFs in ankylosing spines with DISH has been previously reported; [11][12][13][14] however, minimally invasive treatment is desirable due to the high incidence of postoperative complications reported in patients with DISH. 15,16 Although the treatment of ankylosing spinal fractures requires fusion surgery similar to that required for long bone fractures, the indications for BKP in fractures of the terminal or adjacent vertebral bodies of ankylosing spines remain controversial. 9,17 Therefore, the purpose of this study was to determine the poor prognostic factors of BKP for the treatment of fractures of the most distal or distal-adjacent vertebrae of ankylosing spines with DISH.…”
mentioning
confidence: 99%